2017
DOI: 10.1002/rcr2.278
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic left main bronchial rupture: delayed but successful outcome of robotic‐assisted reconstruction

Abstract: Tracheobronchial injuries are rare but life‐threatening conditions in patients with blunt thoracic trauma. The diagnosis and management of such injury may often be delayed due to other concomitant severe injuries. No reported case of a robotic‐assisted bronchial reconstruction has ever been performed for a traumatic bronchial injury. A 23‐year‐old male suffered from traumatic left main bronchial (LMB) rupture with an initial presentation of pneumothorax and pneumomediastinum that eventually progressed to left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Previous studies have demonstrated that patients that underwent open reduction and internal fixation experienced a significant reduction of chest pain and an effective recovery of cough, which aids expectoration [ 20 22 ]. For these patients, getting out of bed early in the postoperative period not only promoted recovery but reduced the incidence of atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that patients that underwent open reduction and internal fixation experienced a significant reduction of chest pain and an effective recovery of cough, which aids expectoration [ 20 22 ]. For these patients, getting out of bed early in the postoperative period not only promoted recovery but reduced the incidence of atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Fizik muayenede, ses kısıklığı, disfoni, afoni, göğüste veya boyunda hava giriş çıkışı olması TBY'yı düşündürür. Hastaların % 87'sinde ciltaltı amfizem görülebilir [3] . Radyolojik bulgular ise pnömotoraks, pnömomediastınum, yaygın ciltaltı amfizem, düşmüş akciğer (fallen lung) görülebilir.…”
Section: Discussionunclassified
“…Cerrahi tedavi yaklaşımlarında, yaralanmanın lokalizasyonuna göre yaklaşımlar servikal veya posterolateral torakotomi şeklindedir. Küçük laserasyonlar primer onarılırken, tam veya kısmi kopmalar hâlinde; enfekte ve nekrotik dokular debride edildikten sonra uç uca anastomoz yapılmalıdır [3] . Sonuç olarak, TBY tanısı gözden kaçabilen mortal bir yaralanmadır.…”
Section: Discussionunclassified
“…Trong đó hay gặp nhất là suy hô hấp (76 -100%) và tràn khí dưới da (87%) có hay không kèm tràn khí màng phổi (17 -70%) (một hay hai bên), dẫn lưu màng phổi không hiệu quả và khí thoát ra nhiều qua dẫn lưu. 1,6,8,9 Hơn nữa, đa số các bệnh nhân thường có những tổn thương phối hợp khác kèm theo (sọ não, bụng, cột sống…), khiến cho việc nhận định triệu chứng nhiều khi khó chính xác. 5 X-quang ngực là phương pháp thăm dò đơn giản và nhanh chóng: Ngoài các dấu hiệu gợi ý như tràn khí màng phổi, tràn khí dưới da, có thể thấy dấu hiệu "phổi rơi" -cần phân biệt với hình ảnh xẹp phổi thụ động do tình trạng tràn khí, có thể hình ảnh phế quản chính ngắt quãng ở rốn phổi trong trường hợp đứt lìa hoàn toàn.…”
Section: Bàn Luậnunclassified